Observational cohort study investigating cognitive outcomes, social networks and well-being in older adults: a study protocol - Johanna Westbrook; Joyce Siette (BMJ Open, 2019)
IntroductionSocial networks play a role in slowing the development of dementia. However, there is a need for further investigation of the effects of improving social networks on health-related quality of life and cognitive performance. Targeted community aged care services are a central strategy for supporting older adults to initiate and maintain their social engagement with other individuals at all stages of later life. This protocol describes a prospective observational cohort study aimed at (1) characterising interpersonal relationships in older adults receiving community care services, (2) assessing the relationship social networks and health-related quality of life and cognition and (3) identifying the association between community care use, social networks and cognition. The findings will contribute to our understanding of how specific social network structures and social support services can maintain cognitive function in community-dwelling older adults.Methods and analysisThis is a prospective, observational cohort study of 201 older Australians residing in the community and receiving care services from one of three aged care organisations. Clients with a history of neurological injury will be excluded. Participants will undergo baseline measures of social networks, health-related quality of life and cognitive function, and a follow-up at 6 months. Service use and sociodemographic variables will also be collected. The primary outcome is cognitive function, and secondary outcomes include social networks and health-related quality of life. Multivariable linear regression will test the hypothesis that increased social networks are associated with an increase in cognitive function.Ethics and disseminationApproval of the study by Macquarie University Research Ethics Committee (reference number 5201831394062) has been obtained. This work will be disseminated by publication of peer-reviewed manuscripts, presentations in abstract form at scientific meetings and results will be made available to home and community-based care older adults and care staff of the involved organisations.Trial registration numberACTRN12618001723279; Pre-results.